Conceptual Foundations and Characteristics of the Institution of the Weaker Party in Civil Relations - Haykyants, Armen; Barseghyan, Tariel (Bulletin of Yerevan University C: Jurisprudence, 2025)
The scientific article is devoted to the analysis of the institution of the “weaker party” in civil relations. A study of foreign and international experience demonstrates that in many legal systems various mechanisms have been developed to ensure the legal protection of the weaker party, with the aim of safeguarding social justice. On a theoretical and methodological basis, the article examines the existing scholarly approaches to the legal protection of the weaker party and identifies the essential features that allow a participant to be classified as such. At the same time, it is emphasized that the scope of these features remains open and may be supplemented by new criteria derived from the principles of good faith, equality, and reasonableness.The article further formulates proposals for improving legal regulation, with the objective of enhancing the threshold of legal protection for the weaker party within the civil law of the Republic of Armenia․
Keywords: weaker party; unfair terms; good faith; equality; reasonableness; balance; characteristics; private; public; concept